2010
DOI: 10.1161/circulationaha.109.896589
|View full text |Cite
|
Sign up to set email alerts
|

Response to Letters Regarding Article, “Risk Factors for Abdominal Aortic Aneurysms: A 7-Year Prospective Study: The Tromsø Study”

Abstract: Reference1. Forsdahl SH, Singh K, Solberg S, Jacobsen BK. Risk factors for abdominal aortic aneurysms: a 7-year prospective study: the Tromsø

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
177
2
10

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(201 citation statements)
references
References 1 publication
12
177
2
10
Order By: Relevance
“…Observations of the current study reveal, in tandem with literature reports on all age cohorts, that hypertension, smoking, and alcohol are the predominant risk factors [15][16][17]. The association of these comorbidities with aneurysms is commensurate with their prevalence among young Africans including Kenyans [18][19][20][21].…”
Section: Comorbid Factorssupporting
confidence: 82%
“…Observations of the current study reveal, in tandem with literature reports on all age cohorts, that hypertension, smoking, and alcohol are the predominant risk factors [15][16][17]. The association of these comorbidities with aneurysms is commensurate with their prevalence among young Africans including Kenyans [18][19][20][21].…”
Section: Comorbid Factorssupporting
confidence: 82%
“…In a recent analysis of the Tromsø Study, 25 variables significantly associated with increased AAA incidence in multivariable analysis were increasing age, male gender, smoking, hypertension, and hypercholesterolemia. In a meta-analysis of population-based screening studies, history of coronary artery disease was also shown to be a risk factor for AAA.…”
Section: Discussionmentioning
confidence: 99%
“…15 Neither is there any evidence that the population scanned has changed: attendance rates in this group of 65-year-old men have remained similar throughout the study. Hypertension, smoking, and hypercholesterolemia have been shown to have a strong association with the development of AAAs 16 and it is suggested that improved medical management of these risk factors is bringing to an end the epidemic of AAAs. 17 This possible reduction is perhaps consistent with other improvements in rates of cardiovascular diseases such as heart attack and stroke 18 and has also been described recently in Sweden, Australia, and New Zealand.…”
Section: Discussionmentioning
confidence: 99%